Ian Stevenson’s "Twenty Cases Suggestive of Reincarnation": An Historical Review and Assessment - Matlock, James (Journal of Scientific Exploration, 2011)
Twenty Cases Suggestive of Reincarnation (first published in 1966) is a classic of 20th-century parapsychology that can still be read with profit. Along with Children Who Remember Previous Lives (2001), it is an ideal introduction to Stevenson. The latter work, intended for the educated general reader, provides an overview of 40 years of research and includes capsule summaries of several cases, but Twenty Cases contains detailed reports that illustrate reincarnation-type cases much more fully. The cases reported in Twenty Cases come from India, Ceylon (now Sri Lanka), Lebanon, Brazil, and the United States (the Tlingit Indians of Alaska). They were selected from about 200 personally investigated by Stevenson in order to show the variety of features this type of case presents. The subjects of all were young children at the time they claimed to have lived before. Collectively these twenty cases help define “cases of the reincarnation type,” as Stevenson came to call them, though they vary substantially in detail.